Oneroom-Babel: poetic technology of coping - Amaral, Beatriz Fernandes Pinheiro do; Donati , Luisa Angélica Paraguai (DAT Journal, 2024)
The article analyzed Sanghee's immersive work OneRoom-Babel (2023) to point out how perceptive processes are technologically conditioned in artistic poetics. It became clear that the incorporations of devices are operational activities of poetic and fundamental to the manifestation of artistic subjectivity. The reflection was based methodologically on the practical dimension of the creation process (Rey, 2002), localizing its technical elements and then appropriating the concepts of body itself (Merleau-Ponty, 1999) and incorporation (Ihde, 2017) to describe the poetic operations. Finally, the reasons that lead the work to be configured as a tactical action were highlighted. (Certeau, 2008).